2007
DOI: 10.1152/ajpregu.00105.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic sleep loss on immune modulation of rats

Abstract: Sleep deprivation is now recognized as an increasingly common condition inherent to modern society, and one that in many ways, is detrimental to certain physiological systems, namely, immune function. Although sleep is now viewed by a significant body of researchers as being essential for the proper working of a host of defense systems, the consequences of a lack of sleep on immune function remains to be fully comprehended. The aim of the current study was to investigate how paradoxical sleep deprivation (PSD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(119 citation statements)
references
References 31 publications
9
109
0
1
Order By: Relevance
“…This result is consistent with studies in rats that demonstrate elevation of baseline glucocorticoid concentrations after 48h of sleep deprivation or 7days of sleep restriction, but not after 24h of sleep deprivation using the modified multiple platform method (Zager et al, 2007).…”
Section: Suppression Of Peripheral and Hypothalamic Inflammation Indesupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with studies in rats that demonstrate elevation of baseline glucocorticoid concentrations after 48h of sleep deprivation or 7days of sleep restriction, but not after 24h of sleep deprivation using the modified multiple platform method (Zager et al, 2007).…”
Section: Suppression Of Peripheral and Hypothalamic Inflammation Indesupporting
confidence: 91%
“…bees (Beyaert et al, 2012), songbirds (Jones et al, 2010), rodents (Zager et al, 2007;Zager et al, 2012)]. A growing body of experimental and epidemiological studies has demonstrated that sleep loss induces alterations in the immune system that predispose individuals towards disease (Faraut et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This same pattern has been observed in humans, total white blood cells (leukocytes) decreasing in depressed patients (Leonard and Song, 1996;Bellingrath et al, 2010). In addition, chronic stress in rats led to a decrease in total leukocyte and lymphocyte counts (Zager et al, 2007). These results therefore suggest that our long-term exposure to unpredictable aversive events may induce a chronic stress state in lambs, characterized among other things by a low granulocyte count.…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown in both humans and laboratory animals that repeated negative emotional experiences can compromise immune function (Leonard and Song, 1996;Zager et al, 2007) and lead to behavioural changes (for a review, Blanchard et al, 2001). In addition, in humans, repeated negative emotional experiences known to induce chronic stress can ultimately heighten fearfulness (Glaser et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep loss is a common condition in new lifestyle while in many instances, its potential adverse impact is under-attended [6]. Based on the experimental and population-based evidence, sleep restriction may generate numerous changes in the body, such as memory defects [7], hormonal [8], immunological abnormalities [9,10] and impaired motor activity [11]. Meanwhile, the exact mechanism through which impaired sleep affects such functions needs to be further explained.…”
Section: Introductionmentioning
confidence: 99%